"Metal-free" synthesis of 1, 2, 3-triazoles via tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of ethyl acrylate derivatives. Issue 24 (13th June 2018) - Kumar, B. Senthil; Gadakh, Sunita; Sudalai, Arumugam
Graphical abstract: Highlights: Single step, high yield synthesis of 1, 2, 3-triazoles. α, β-unsaturated esters have been used as substrates. Azide had been added across CC bond intramolecularly under cycloaddition mode. "Metal free" synthesis. High regio and distereoselectivity. Abstract: An efficient "one-pot" method for the synthesis of substituted 1, 2, 3-triazole derivatives in excellent yields as single regioisomer is reported. The key transformation involves an atom-efficient tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of acrylate derivatives on treatment with NaN3 in DMF under mild conditions.